The Spanish labor crisis and Strategy Sustainable Growth (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Based on the latest data from the survey conducted by the National Institute of Statistics (INE) on the working population in Spain, which shows the seriousness of the labour crisis in Spain, this paper describes its structural nature. In order to face this serious problem, which has no solution in the short term, the paper supports that it is essential to change the Spanish productive model through structural reforms that improve not only the expenditure pattern and socio-economic frameworkbut also the institutions of the labour market. The Strategy for SustainableGrowth, recently made public by the Spanish Government, could drive the structuralreforms necessary to solve the labour problem in the medium to long term.
Keywords: Spanish labour market; Spanish productive model; expenditure pattern; Strategy of Sustainable Growth.